Upregulation of HO‐1 with Haemin Alleviates LPS‐Stimulated Pro‐inflammatory Responses Through Downregulation of p38 Signalling Pathways in Rat Liver. (November 2015) - Tang, J.; Li, L.; Li, C.‐M.; Wu, J.; Sun, Y.; Wang, G.‐L.
Abstract Haem oxygenase‐1 (HO‐1) plays an important role in inflammatory disease development and progression. Whether it has an anti‐inflammatory role in lipopolysaccharide (LPS)‐induced liver injury remains unclear. To investigate the functional role of HO‐1 in protecting liver tissue against inflammatory response stimulated by LPS in rat and the mechanism by which it achieves this protective effect, LPS‐stimulated inflammatory models were established. In pretreatment of rats with HO‐1 activator (haemin) or inhibitor (zinc protoporphyrin‐9, ZnPP, a specific inhibitor of HO) before LPS stimulation, we evaluated the pathological changes by haematoxylin–eosin staining. The mRNA expression and secretion of IL‐1β and IL‐6 in rat liver were analysed using the real‐time PCR and ELISA. Real‐time PCR and Western blot were also used to evaluate the expression of HO‐1, p38 and p‐p38 in liver. Liver CO contents were sensitized to the expression of HO‐1. Induction of HO‐1 by haemin remarkably inhibited the expression of p38, and addition of ZnPP increased this expression. Our results demonstrate that HO‐1 is an anti‐inflammation factor in LPS‐stimulated liver, which regulate the inflammatory response through downregulation of p38 signalling pathways in rat liver.